2017
DOI: 10.1073/pnas.1617640114
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone signaling underlies the pea aphid transgenerational wing polyphenism

Abstract: The wing polyphenism of pea aphids is a compelling laboratory model with which to study the molecular mechanisms underlying phenotypic plasticity. In this polyphenism, environmental stressors such as high aphid density cause asexual, viviparous adult female aphids to alter the developmental fate of their embryos from wingless to winged morphs. This polyphenism is transgenerational, in that the pea aphid mother experiences the environmental signals, but it is her offspring that are affected. Previous research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 58 publications
3
102
0
Order By: Relevance
“…Therefore, given the level of sequence divergence between the corresponding M. persicae genes and the Be. tabaci ecdysone receptor and P. solenopsis chitin synthase constructs (Table S1), the RNAi effects on the expression levels of these genes are likely to be more minor than those observed with M. persicae cathepsin L. Moreover, we did not observe the morphological phenotypes that were previously reported when silencing ecdysone receptor or chitin synthase expression (Zhu et al , ; Khan et al , ; Shang et al , ; Yan et al , ; Vellichirammal et al , ; Zhao et al , ), and the identified protein accumulation deficit is more similar to what one would expect from silencing the expression of a gut protease.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Therefore, given the level of sequence divergence between the corresponding M. persicae genes and the Be. tabaci ecdysone receptor and P. solenopsis chitin synthase constructs (Table S1), the RNAi effects on the expression levels of these genes are likely to be more minor than those observed with M. persicae cathepsin L. Moreover, we did not observe the morphological phenotypes that were previously reported when silencing ecdysone receptor or chitin synthase expression (Zhu et al , ; Khan et al , ; Shang et al , ; Yan et al , ; Vellichirammal et al , ; Zhao et al , ), and the identified protein accumulation deficit is more similar to what one would expect from silencing the expression of a gut protease.…”
Section: Discussionmentioning
confidence: 50%
“…Based on what is known about the RNAi, four mismatches in the centre of a sequence should eliminate expression silencing. RNAi of ecdysone receptor expression resulted in moulting defects in several insect species and, in particular, caused more frequent wing formation in aphids (Zhu et al , ; Yan et al , ; Vellichirammal et al , ). We did not observe such a phenotype in our M. persicae experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This method leads to considerable environmental pollution and health hazards for farmers, as well as significantly increasing the costs of wheat production. Now a plant‐mediated RNA interference (RNAi) strategy has been shown to be effective for the development of aphid‐resistant germplasm or cultivars . However, we found no published reports of using a gene involved in olfactory perception to control wheat aphid in field.…”
Section: Introductionmentioning
confidence: 90%
“…Now a plant-mediated RNA interference (RNAi) strategy has been shown to be effective for the development of aphid-resistant germplasm or cultivars. [5][6][7][8] However, we found no published reports of using a gene involved in olfactory perception to control wheat aphid in field.…”
Section: Introductionmentioning
confidence: 99%
“…The result partly confirmed the role of octopamine in the regulation of wing dimorphism in the pea aphids. A subsequent study demonstrated that ecdysone signaling pathway is also involved in the transgenerational wing determination (Vellichirammal, Gupta, Hall, & Brisson, ). Females injected with ecdysone or its analog produced more winged offspring.…”
Section: Introductionmentioning
confidence: 99%